Nexus between weeds secondary succession and livelihoods in Hadejia-Nguru wetlands of Nigeria - Abubakar Ahmed Jajere; Abubakar Muhammad Saidu; Usman Adamu; Usman Ibrahim (Center for Science and Technology, IAIN Surakarta, 2023)
Hadejia-Nguru wetlands is known as a joule of the Sahel as it is the major biodiversity reservoir of the Sahelian parts of Nigeria. However, series of impediment that follows the Sahelian drought of 1970s has been altering the ecosystem of the wetlands. The secondary succession of invasive weed that follow the habitat changes has altered the wetlands derived livelihood activities. This study examines the livelihoods constrain of the weeds as well as livelihoods derived from the weeds. Information on biodiversity timeline history, types of weeds that grow on the wetland site, the livelihoods activities derived from the weeds, and the livelihoods constraint of weeds were collected through interviews with key informants and focus group discussion. Three focus group discussions were conducted in six wetlands site communities, with participants including farmers, pastoralists, and other categories of wetland users. The qualitative information collected was analysed using grounded theory tool. The study identified 18 weed species that grow on the Hadejia-Nguru wetlands and discovered that the weeds are sources of raw materials for constructions, craft work, and fodder for animals among others. They also constitute the major constraints to livelihood activities such as fishing, transportation, irrigation, rainfed farming, and domestic water supply, among others. The study concluded that weeds are both a constraint and means of livelihood. Hence, the study’s hypothesis is that ‘’the impact of weeds on livelihoods diminish over time’.’ It is therefore recommended that all the beneficial weeds in the wetlands should be identified and utilized sustainably, while the growth of the bad ones should be controlled.